Krubbitning hos häst på olika strömaterial - Helldén, Maria (SLU/Dept. of Animal Environment and Health (until 231231), 2007)
By limiting our horse's freedom of movement, we restrict their opportunity to forage, which is one of their most important needs. If their need of forage is not fulfilled it can lead to frustration, which might manifest itself in abnormal behaviour, like the oral stereotypies for example crib-biting. It is a held belief that the horse swallows air while crib-biting, which they don't, and that swallowed air causes colic, and the belief that other horses can copy the behaviour, leads to the use of many methods to prevent the behaviour. Cribbing-collar, operations, electrified ledges and bad tasting solutions are methods to prevent the performance of crib-biting. As new studies indicate that the function of the behaviour is to ameliorate underlying problems, the methods can do more harm than good and decrease welfare. Methods used often address symptoms rather than underlying causation.